Integrasi Himpunan Dan Al-Qur’an Serta Implementasinya Dalam Pembelajaran Matematika - Ainul Fitri; Rizqiya Hasanah; Sofhia Vabiola; Mia Yolanda Utami Putri; M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2023)
Mathematics is also in two positions, namely between the real world and the unseen world so that mathematics which does not exist in the real world has an abstract object and mathematics which is not in the unseen world so that the object is not an